PENGARUH BRAND IMAGE, TRUST, DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN KOPI KAPAL API DI KECAMATAN PANJI - Arisusanto, Maulana Febri; Syahputra, Hendra; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
PT Santos Jaya Abadi is a multinational company with a focus on producing packaged coffee such as Kapal Api coffee and other packaged beverages. The TBI data above shows that Kapal Api packaged coffee has the best survey among other competitors of ground coffee with pulp. So the focus of this study is on Kapal Api packaged coffee consumers in Panji District, Situbondo Regency. The population in this study was the entire community of Panji District. The sampling technique was determined by Purpove sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the SMART PLS 3.2.8 application, show that Brand image has a positive but insignificant effect on Consumer Satisfaction, Trust and Product Quality have a significant positive effect on Consumer Satisfaction, Brand image, Trust and Product Quality have a positive but insignificant effect on Repurchase Intention, Consumer satisfaction has a significant positive effect on Repurchase Intention, Brand Image has a positive but insignificant effect on Repurchase Intention through Consumer Satisfaction, Trust and Product Quality have a significant positive effect on Repurchase Intention through Consumer Satisfaction.